2015
DOI: 10.5851/kosfa.2015.35.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Allium hookeri Root Extract and Its Effect on Lipid Stability of Sulfur-fed Pork Patties

Abstract: This study was performed to assess the antioxidant activity of Allium hookeri root extract (AHE) on lipid oxidation of raw sulfur-fed pork patties for 14 d of refrigerated storage. Different concentration of ethanol (0-100%) and time (1-12 h) were applied to determine the extraction condition. Water (0% ethanol) extraction for 1 h was selected as an optimal extraction condition of AHE for the following study showing the highest total phenolic content and total flavonoid content, as well as the strongest antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Similar results showed an antioxidant effect from sulfur-fed pork applied to meat products. (Cho et al , 2015; Kim et al , 2015). Also, the higher value of TBA meat products have, rancid odor increased, the sensory quality of meat product might be negatively affected (Younathan and Watts, 1959).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results showed an antioxidant effect from sulfur-fed pork applied to meat products. (Cho et al , 2015; Kim et al , 2015). Also, the higher value of TBA meat products have, rancid odor increased, the sensory quality of meat product might be negatively affected (Younathan and Watts, 1959).…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was also reported by Zhang H and others (). Cho and others () evaluated the effect of different concentrations of Allium hookeri root extract (AHE) on the lipid oxidation and color stability of raw sulfur‐fed pork patties during 14 d of refrigeration, and they found that the CD and TBARS values decreased proportional to the increase of AHE level and inhibited meat discoloration. In that paper, Cho and others () suggested that AHE polyphenols could be used to extend the shelf‐life of food.…”
Section: Polyphenols As Antioxidants To Improve Stability To Oxidatiomentioning
confidence: 99%
“…Cho and others () evaluated the effect of different concentrations of Allium hookeri root extract (AHE) on the lipid oxidation and color stability of raw sulfur‐fed pork patties during 14 d of refrigeration, and they found that the CD and TBARS values decreased proportional to the increase of AHE level and inhibited meat discoloration. In that paper, Cho and others () suggested that AHE polyphenols could be used to extend the shelf‐life of food. Zhang Y and others () prepared pork salami using an extract rich in flavonoids obtained from rape ( Brassica campestris L.) bee pollen (RBP) as an antioxidant.…”
Section: Polyphenols As Antioxidants To Improve Stability To Oxidatiomentioning
confidence: 99%
“…Allium species have been used as traditional medicine and health-promoting foods [3,4,11]. Allium hookeri (A. hookeri), a member of Liliaceae family, is widely found in Sri Lanka, India, China and Bhutan, and has anti-oxidant and anti-inflammatory activities [3,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Allium hookeri (A. hookeri), a member of Liliaceae family, is widely found in Sri Lanka, India, China and Bhutan, and has anti-oxidant and anti-inflammatory activities [3,7,12]. Water extract of A. hookeri protected oxidative stress-mediated inflammatory responses and pancreatic β-cell damage in streptozotocin-induced diabetic rats [12].…”
Section: Introductionmentioning
confidence: 99%